Analisis Half-Wave dan Full-Wave Rectifiers Menggunakan Circuit Lab Online - Alpiyan Arif Rojabi; Hana Fatimah Zahra; Pramudika Afriza Fahmi; Nuriah Fadhilaturachman; Diva Nuranty Yovanka; Muhammad Rifyal (Lembaga Penelitian Universitas Balikpapan, 2023)
Functioning as a current rectifier, the presence of a diodeas an active electronic component cannot be separated in life. Therectifier function of this diode is also known as a rectifier whichworks by converting the alternating current (AC) from a device todirect current (DC). The rectifier can be used in half wave rectifierand full wave rectifier circuits This study aims to analyze moredeeply about the signal output of a half-wave rectifier circuit and theeffect of attention value on the output signal of a full-wave rectifiercircuit. The research was conducted using a literature studyapproach and verification through online experiments using aCircuit Lab simulator. After doing research, it is known that thesignal issued by a half-wave rectifier circuit has no valleys. Whereasin a full wave rectifier circuit it is known that the values have aninfluence on the output signal.